What buildings policy might look like if we took climate change seriously - Fawcett, T; Topouzi, M (IOP Publishing, 2019)
In 2018, the Intergovernmental Panel on Climate Change released its report on the impacts of global warming of 1.5°C. It called for "rapid, far-reaching and unprecedented changes in all aspects of society" to reduce the risks of increasing climate change. Energy use in buildings is one of the key contributors to greenhouse gas emissions in the UK and EU. Detailed policies to support high standards in new build and acceleration of ambitious retrofit are a necessary part of any serious response to climate change.